Aflatoxin B1 Induced Oxidative Stress and Gut Microbiota Disorder to Increase the Infection of Cyprinid Herpesvirus 2 in Gibel Carp (Carassius auratus gibelio) - Mingyang Xue; Miao Fu; Mengwei Zhang; Chen Xu; Yan Meng; Nan Jiang; Yiqun Li; Wenzhi Liu; Yuding Fan; Yong Zhou (MDPI AG, 2023)
Aflatoxin contamination of food and water is a serious problem worldwide. This study investigated the defensive ability of gibel carp exposed to aflatoxin B1 (AFB1) by challenging it with cyprinid herpesvirus 2 (CyHV-2) infection. The data showed that AFB1 exposure significantly increased the mortality of CyHV-2-infected gibel carp, and enhanced the viral load in the fish liver, kidney, and spleen. The oxidative-antioxidant balance suggested that AFB1 induced severe oxidative stress, including increased reactive oxygen species (ROS) and malondialdehyde (MDA) levels in the AFB1 exposed group, and the reduced activity of superoxide dismutase (SOD), glutathione-S-transferase (GST) and catalase (CAT) in the AFB1 exposed group. Meanwhile, the related expression of nuclear factor erythroid 2-related factor 2 (Nrf2), interferon regulatory factor 3 (IRF3) and the type 1 interferon (IFN1) were noticeably down-regulated, but caspase-1 was up-regulated, after exposure to AFB1, demonstrating that fish are unable to avoid the virus infection. It should be noted that the intestinal microbiota diversity and richness were lower in the AFB1 exposed group, and the composition of intestinal microbiota was affected by AFB1, resulting in the higher abundance of bacteria (such as Aeromonas and Bacteroides) and the lower abundance of potentially beneficial bacteria (such as Cetobacterium and Clostridium) in the AFB1 exposed group. This research provides insight into the possibility that AFB1 may increase the susceptibility of C. gibelio to CyHV-2 infection, and thus amplify the viral outbreak to endanger ecological safety in aquatic environment.